How to estimate nanoaerosol explosion risk? - Bouillard, Jacques (Nanosafe, 2008)
"Main results: To evaluate nanopowder safety characteristics, morphologic, surface and bulk properties as well as their potential to disperse in their environment have to be characterized. Most nanopowders can display high reactivity characteristics that can lead to fire or explosion accidents. Specific tools and protocols are necessary to assess these parameters. Environmental and process factors (flow velocities, materials fluxes and inventories, Pressures , Temperatures and concentrations) are key elements to consider in the risk assessment. Once the risk evaluated, one can propose various types of safety barriers to reduce the risk: - A Prevention barrier to reduce the probability of occurrence of an accident. - A Mitigation barrier to reduce the effects of process parameters or propose product substitution or severity attenuation. - A Protection barrier, such as protection equipments, confinement technologies or venting system, to protect the worker or the environment. "